1987
DOI: 10.1042/bj2460725
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine (Desferal) and superoxide free radicals. Formation of an enzyme-damaging nitroxide

Abstract: In neutral solutions, desferrioxamine (Desferal) can react with the superoxide free radical, O2.- (possibly through its protonated form HO2.), to form a relatively stable nitroxide free radical, which can have a half-life of approx. 10 min at room temperature. The formation of the radical can be largely prevented by the presence of superoxide dismutase. The radical reacts rapidly with cysteine, methionine, glutathione, vitamin C and a water-soluble derivative of vitamin E. It also reacts rapidly with alcohol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…The main target of free radicals are lipids, nucleic acids, carbohydrates and proteins. As a result of oxidative reactions, proteins undergo proteolysis, structural changes, aberrant aggregation and oxidation of the side chains of amino acids [26,27]. Indeed, modifications of protein molecular weight due to the formation of intramolecular bonds and their cleavage into peptides have been consistently reported [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main target of free radicals are lipids, nucleic acids, carbohydrates and proteins. As a result of oxidative reactions, proteins undergo proteolysis, structural changes, aberrant aggregation and oxidation of the side chains of amino acids [26,27]. Indeed, modifications of protein molecular weight due to the formation of intramolecular bonds and their cleavage into peptides have been consistently reported [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of oxidative reactions, proteins undergo proteolysis, structural changes, aberrant aggregation and oxidation of the side chains of amino acids [26,27]. Indeed, modifications of protein molecular weight due to the formation of intramolecular bonds and their cleavage into peptides have been consistently reported [26,27]. Sulphurcontaining amino acids such as cysteine and methionine are more susceptible to ROS attack [28].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of effect of DTPA could be explained by the iron-DTPA complex continuing to catalyse oxygen radical generation [28]. Conversely, the effect of deferoxamine may be explained by the ability of this compound to scavenge free radicals, including O # d − [29], rather than sequester iron. Thus, whereas metal con- taminants are still good candidates, unambiguous evidence for their involvement is difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Laser settings were identical for acquisition of all images from control and diabetic specimens. It has been reported that desferrioxamine at high concentrations in vitro can react with superoxide to form a nitroxide free radical (36,37). To determine whether HES-DFO acutely reacts with superoxide produced by vessels, we preincubated epineurial vessels from a diabetic rat with 1 mmol/l, 100 mol/l, or 10 mol/l HES-DFO or hydroxyethyl starch alone for 30 min.…”
mentioning
confidence: 99%